Understanding environmental pollution : - Hill, Marquita K. (Cambridge University Press, 2004)
This well-received textbook delivers a concise overview of global and individual environmental pollution for undergraduate courses, presenting students with the tools to assess environmental issues. With more than thirty percent new material, Hill assesses pollution from an international perspective, including air and water pollution, global warming, energy, solid and hazardous waste, and pollution at home. Both the sources and impacts of pollution are addressed, as well as governmental, corporate, and personal responsibility for pollution, and pollution prevention is emphasized throughout. Non-technical language encourages greater understanding of these often complex issues, and thought-provoking 'Delving Deeper' exercises are included, increasing engagement with the text and enabling students to apply what they have learned. A new chapter on the chemistry basics of pollution links to sections on toxicology and risk assessment, helping students understand concerns over chemicals and their regulation. An essential review of environmental pollution for environmental science students.